The Effect of Perceived Quality, Customer Satisfaction on Physical Evidence, and Brand Image on Patient Loyalty at the Emdee Skin Clinic Palembang Beauty Clinic - Sheisa Marinka; Oscar Jayanagara (Eduvest - Journal of Universal Studies, 2025)
e beauty industry in Indonesia, including The Emdee Skin Clinic Palembang, is rapidly growing, yet faces challenges in maintaining patient loyalty, as evidenced by a 15.73% decrease in repeat visits from 2023 to 2024. This study investigates the influence of perceived quality, physical evidence, brand image, and customer satisfaction on patient loyalty. Using a quantitative approach with a Likert scale, 200 respondents who had undergone treatment more than once at the clinic were surveyed. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived quality and physical evidence positively affect brand image and patient loyalty. Additionally, brand image significantly mediates the relationship between perceived quality and physical evidence on patient loyalty. This study highlights the importance for clinic managers to enhance service quality, improve facilities, and build a strong brand image to retain patient loyalty. Future research should focus on extending the data collection period, incorporating more variables, and involving a more diverse respondent pool.